Fragility fracture risk in cirrhosis: a comparison of the fracture risk assessment tool, British Society of Gastroenterology and National Institute for Health and Clinical Excellence guidelines. Issue 4 (12th July 2012) - Ayres, Lachlan Richard Owen; Clarke, Shane; Digby-Bell, Jonathan; Dhanda, Ashwin Deep; Dharmasiri, Suranga; Caddick, Katharine; Collins, Peter Lesley
Abstract : Objective: Low bone mineral density (BMD) is common in chronic liver disease and predisposes to fracture. We aimed to compare British Society of Gastroenterology (BSG) and National Institute for Health and Clinical Excellence (NICE) osteoporosis guidelines with the fracture risk assessment tool (FRAX). FRAX is a web-based algorithm used to estimate fracture risk with or without dual-emission x-ray absorptiometry (DXA). Pre-BMD FRAX categorises patients to low, intermediate or high risk according to thresholds set by the National Osteoporosis Guidelines Group (NOGG) and recommends lifestyle advice, DXA or anti-osteoporosis treatment, respectively. Design: The guidelines were applied to 132 patients with cirrhosis (91% Child–Pugh A). The number that would require DXA and be recommended treatment was determined. Using post-BMD FRAX/NOGG as a reference point, high-risk patients not recommended treatment and low-risk patients treated 'unnecessarily' were identified. Results: BSG guidelines were applicable to 100% of the cohort, 88% required DXA and 30% would be recommended treatment. Equivalent figures for NICE guidelines were 30%, 17% and 12%, and for FRAX/NOGG guidelines were 78%, 27% and 15%, respectively. Using BSG guidance 8% of high-risk patients were not recommended treatment and 62% of those treated were low risk, compared with NICE: 3%, 60% and FRAX/NOGG: 13%, 40%, respectively. Conclusion: For patients with Child–Pugh A cirrhosis BSG guidelines are the most inclusive, but have high cost implications in terms of DXA scanning and unnecessary treatment. Risk stratification using FRAX requires fewer DXA scans with minimal impact in terms of missing high-risk patients, and yields a modest reduction in unnecessary treatment.